Bibliometrics and ‘core journals’ in the Humanities: an Italian case study - Lanzillo, Luca (Qualitative and Quantitative Methods in Libraries, 2017)
This paper analyses possible transformations in the publication behaviour of Italian humanistic researchers as a results of national research assessment exercises (VQR 2004-2010) and national habilitation exams for academic career (ASN 2012 and 2013). Case study is the humanists‟ community of Sapienza University of Rome, a representative sample of Italian context. In particular, this paper examines the use of scientific journals in the last ten years (2004-2014), before and after introduction of a journal rating system. Aim of this research is to verify, through experiment with Sapienza institutional database, if the number of journals selected as outputs by this scholarly community have been changed over the years, producing a more restricted set of “core” journals with a greater scientific strength.